Fumonisins and Alternaria alternata lycopersici toxins: sphinganine analog mycotoxins induce apoptosis in monkey kidney cells. - Wang, W (1996)
Fusarium moniliforme toxins (fumonisins) and Alternaria alternata lycopersici (AAL) toxins are members of a new class of sphinganine analog mycotoxins that occur widely in the food chain. These mycotoxins represent a serious threat to human and animal health, inducing both cell death and neoplastic events in mammals. The mechanisms by which this family of chemical congeners induce changes in cell homeostasis were investigated in African green monkey kidney cells (CV-1) by assessing the appearance of apoptosis, cell cycle regulation, and putative components of signal transduction pathways involved in apoptosis. Structurally, these mycotoxins resemble the sphingoid bases, sphingosine and sphinganine, that are reported to play critical roles in cell communication and signal transduction. The addition of fumonisin B1 or AAL toxin, TA, to CV-1 cells induced the stereotypical hallmarks of apoptosis, including the formation of DNA ladders, compaction of nuclear DNA, and the subsequent appearance of apoptotic bodies. Neither mycotoxin induced cell death, DNA ladders, or apoptotic bodies in CV-1 cells expressing simian virus 40 large T antigen (COS-7) at toxin concentrations that readily killed CV-1 cells. Fumonisin B1 induced cell cycle arrest in the G1 phase in CV-1 cells but not in COS-7 cells. AAL toxin TA did not arrest cell cycle progression in either cell line. The induction of apoptosis combined with the widespread presence of these compounds in food crops and animal feed identifies a previously unrecognized health risk to humans and livestock. These molecules also represent a new class of natural toxicants that can be used as model compounds to further characterize the molecular and biochemical pathways leading to apoptosis.